A study assessing the knowledge, attitude, and practice of materiovigilance among medical professionals in the states of Tamil Nadu and Andhra Pradesh, India - K., Saranraj; P., Usha Kiran (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Medical devices are vital for healthcare diagnosis and treatment but pose inherent risks. Physicians and healthcare professionals play a crucial role in reporting adverse events associated with these devices. Despite this, there is a notable scarcity of literature addressing the knowledge, attitudes, and practices surrounding India's Materiovigilance (Mv) Program. This study aimed to evaluate the knowledge, attitudes, and practices of doctors and postgraduate residents in Andhra Pradesh and Tamil Nadu regarding the Materiovigilance program of India (MvPI). Methods: It was conducted as an observational, cross-sectional study, a structured self-administered Google Form survey was distributed among medical professionals and citizens of Andhra Pradesh and Tamil Nadu. The survey, comprising 22 questions on knowledge, attitudes, and Mv practices, was disseminated via various social networking sites. Results: Out of 700 doctors and postgraduate residents surveyed, 496 responded, yielding a response rate of 70.8%. The majority (96.8%) acknowledged the potential for adverse events from medical devices, with 91.1% agreeing on healthcare professionals' responsibility to report such events. Despite experiencing medical device-related adverse events in practice (63.3% of respondents), only a small fraction (12.1%) reported them, although 93.5% expressed willingness to report. Conclusions: The study underscores a knowledge gap among physicians and residents regarding MvPI in India, highlighting the necessity for educational interventions. To address this gap, MvPI coordinators should organize conferences and seminars aimed at enhancing awareness and reporting practices among healthcare professionals.